2016
DOI: 10.1177/0886260515625908
|View full text |Cite
|
Sign up to set email alerts
|

We Are Family: Specifying the Unique Contribution of Abuse and Neglect of Siblings on the Prevalence, Severity, and Chronicity of Maltreatment in the Household

Abstract: Prior research typically focuses on a single child ("index" victim) when measuring child abuse and neglect (CAN) using Child Protective Services (CPS) records. However, excluding siblings has the potential to underestimate estimates of the prevalence, severity, and chronicity of CAN in the household, which includes all children in the family. CPS maltreatment records were searched in 2005 for 366 "index" victims who were surveyed for 5 consecutive years (from 1998 to 2002) for the Mobile Youth Survey (MYS) as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…However, when considerin g the family mean and relative level of CM a slightly different picture emerges. The family-wide effects of CM on an individual may be either direct, by being exposed to the same adverse parental behavior, or indirect, the so-called vicarious effect of CM (Spano, 2018 ). For EM, both the family means and relative levels (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when considerin g the family mean and relative level of CM a slightly different picture emerges. The family-wide effects of CM on an individual may be either direct, by being exposed to the same adverse parental behavior, or indirect, the so-called vicarious effect of CM (Spano, 2018 ). For EM, both the family means and relative levels (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…getting hit or kicked by a parent), could also affect siblings indirect by being the spectator, i.e. the vicarious effect of abuse (Spano, 2018 ). Thus, a key question we aim to investigate is whether CM reported by siblings growing up together (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The author of a later US study of 366 youth found that some families were the subject of multiple reports, although there was less information on the level of increased risk and for which specific maltreatment type. 7 Of the 3 remaining studies of sibling maltreatment, 2 were focused specifically on physical abuse 8 or children who were severely abused, 9 whereas the third involved interviews with 59 sibling pairs to assess reports of neglectful parenting. 10 The authors of these studies all reported that siblings of children who were maltreated were more likely to experience physical or severe abuse.…”
mentioning
confidence: 99%
“…Familial genetic variants explain part of the variance in adolescent cognitive development (Dickinson et al, 2019). Shared environmental circumstances, including shared trauma, or family financial stability may also add to development of familial cognition (Gottschling et al, 2019; Hakulinen, Webb, Pedersen, Agerbo, & Mok, 2020; Mansueto, Schruers, Cosci, & van Os, 2019; Spano, 2018). Cognition then may mediate the relationship between these exposures and symptomatic outcomes in psychosis, exerting the strongest effect on disorganization (Mansueto et al, 2019).…”
Section: Discussionmentioning
confidence: 99%